Fungi associated with the red mangrove Rhizophora mangle (Rhizophoraceae) in Cozumel Island Biosphere Reserve, Quintana Roo, Mexico - García-Martínez, Yenitze; Heredia Abarca, Gabriela; Guzmán-Guillermo, Jorge; Valenzuela, Ricardo; Raymundo, Tania (Instituto de Ecología, A.C., 2021)
Background and Aims: Mangroves provide ecological and economic benefits. In addition they harbor a great diversity of organisms, among which fungi, which because of their versatility proliferate both on plant rests and living vegetation in these ecosystems. However, the current knowledge about these organisms in Mexican mangroves is still scarce. Therefore, the principal goal of this paper is presenting the fungal richness associated with Rhizophora mangle, one of the dominant tree species in the mangroves of the Mexican Caribbean.Methods: During the year 2019 fungal specimens were collected developing on living and dead branches, fallen trunks, roots and litter. The collections were made in patches with populations of R. mangle in the Cozumel Island Biosphere Reserve. The taxonomic determination was carried out according to traditional techniques in mycology. The specimens are deposited in the herbarium of the Universidad Veracruzana (XALU) and in the fungi collection of the Escuela Nacional de Ciencias Biológicas (ENCB). Key results: Twenty fungi species were determined on different structures of R. mangle. Nineteen new records are presented for the Cozumel Island, while Arthonia conferta, Halorosellinia oceanica, Phyllosticta capitalensis, Pseudocamarosporium propinquum and Chaetosphaerella fusca are new records for Mexico. The class Arthoniomycetes presented the highest taxonomic richness. The substrate with the highest richness and abundance was branch bark.Conclusions: Ascomycota was the dominant fungus group. The best represented habits are lignicolous saprobes and lichenized epiphytes.